Dynamics of Lake Sturgeon (Acipenser fulvescens Rafinesque, 1817) in a 'pristine' river. (1st December 2017) - Haxton, T.; Friday, M.; Gillespie, M.
Summary: Lake Sturgeon, Acipenser fulvescens, was assessed in a large, pristine river in northern Canada using a standardized protocol. Gill netting (38‐127 mm and 204‐306 mm stretched mesh) was conducted at five sites averaging 37 rkm in the Attawapiskat River in Ontario. The objectives were to ascertain relative abundance of Lake Sturgeon within a northern river; determine if Lake Sturgeon are randomly distributed within a 'pristine' river; assess if there is evidence of spatial structuring; and determine if there is genetic structuring within the river. Over the two years (2015 and 2016), 176 Lake Sturgeon were sampled with a mean total length of 851.1 mm (323.4 SD ) and mean age of 21 years (12.2 SD ). There was a significant difference in the mean total length of the Lake Sturgeon caught, with larger sturgeon in the upstream sites and smaller sturgeon in the downstream sites, signifying a spatial segregation of life stages within the Attawapiskat River. One hundred and fifty‐four Lake Sturgeon were genotyped at 10 or more loci. There was no evidence of genetic divergence among sites or population structuring. In fact, parent‐offspring relationships were determined using COLONY between upstream and downstream sites, a minimum distance of approximately 190 rkm. This study represents the first to assess a Lake Sturgeon population systematically using a standardized index approach at multiple sites in a 'pristine' river. It demonstrated the importance of a holistic approach to the river at a larger scale and a better understanding of life history requirements for conservation. For example, if only one of the upper sites were assessed, it might have been interpreted as the idyllic 'old growth' population with limited or no recruitment. The corollary from sampling only lower sites would be identifying a lack of adults and potentially erroneously declaring an overexploitation concern. This stresses the importance of a larger scale approach for assessing 'pristine' rivers and not using a small scale approach to make large scale inferences.